The Impact Of Carbon Capture And Storage On A Decarbonized German Power Market - Stephan Spiecker; Volker Eickholt (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
The European energy policy is substantially driven by the target to reduce the CO2-emissions significantly and to mitigate climate change. Nevertheless European power generation is still widely based on fossil fuels. The carbon capture and storage technology (CCS) could be part of an approach to achieve ambitious CO2 reduction targets without large scale transformations of the existing energy system. In this context the paper investigates in how far the CCS-technology could play a role in the European and most notably in the German electricity generation sector. To account for all the interdependencies with the European neighboring countries, the embedding of the German electricity system is modeled using a stochastic European electricity market model (E2M2s). After modeling the European side constraints, the German electricity system is considered in detail with the stochastic German Electricity market model (GEM2s). The focus is thereby on the location of CCS plant sites, the structure of the CO2-pipeline network and the regional distribution of storage sites. Results for three different European energy market scenarios are presented up to the year 2050. Additionally, the use of CCS with use of onshore and offshore sites is investigated.
Keywords: Q3; Q4; C61; 330; stochastic optimization; carbon capture and storage; power system economics